Protective Effect of Beta-Carotene against Myeloperoxidase- Mediated Oxidative Stress and Inflammation in Rat Ischemic Brain Injury - Hassan N. Althurwi; Rehab F. Abdel-Rahman; Gamal A. Soliman; Hanan A. Ogaly; Faisal K. Alkholifi; Reham M. Abd-Elsalam; Saleh I. Alqasoumi; Maged S. Abdel-Kader (MDPI AG, 2022)
Oxidative stress and inflammatory reaction play critical roles in ischemia/reperfusion (I/R) injury in the brain. β-carotene (βCAR) is a naturally occurring pigment present in fruits and vegetables that expresses antioxidant and anti-inflammatory activities. This study was conducted to investigate the involvement of Bcl2/Bax and NF-κB signaling pathways in the potential protective role of βCAR against brain injury in a middle cerebral artery occlusion (MCAO) rat model. A focal brain ischemia model was created for 2 h, followed by reperfusion. Rats were given 10 and 20 mg/kg of βCAR for 7 days orally before induction of ischemia, at the start of reperfusion, and 3 days after ischemia. Scores of neurological deficit were rated 24 h after induction of ischemia. Motor coordination and spontaneous coordinate activities were assessed using rotarod and activity cage, respectively. After 2 h of the last dose, the animals were killed and their brains were extracted for further examinations. The results of the study show that βCAR diminished the score of neurological deficits and ameliorated motor coordination, balance, and locomotor activity in the I/R control group. Further, βCAR resulted in diminution of malondialdehyde (MDA) and augmentation of reduced glutathione (GSH) contents, as well as the elevation of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) enzyme activities in the brain homogenates of I/R rats. βCAR treatment significantly reduced nuclear factor kappa B (NF-κB) brain content and myeloperoxidase (MPO) activity and ameliorated the histological alterations in the brain tissues. βCAR significantly suppressed Bcl-2-associated X protein (Bax) and caspase-3 expression, as well as upregulated B-cell lymphoma-2 (Bcl-2) expression, suggesting a neuroprotective potential via downregulating NF-kB and protecting the rat brain against the I/R-associated apoptotic injury.